Vietnam Labyrinth : Allies, Enemies, and Why the U.S. Lost the War - Tran, Chau Ngoc, 1924-; Fermoyle, Ken, 1927- (Book collections on Project MUSE., 2012)
"The memoir of Tran Ngoc Chau, one of the few Vietnamese Army officers who also saw service in Ho Chi Minh's National Liberation Army"--Provided by publisher.